A study on Malaysia's obligation to implement international humanitarian law / Tengku Muhammad Aiezuddin Shah, Zaznuriah Mohd Zahir and Sara Zuriati Zaharifudin. - Shah, Tengku Muhammad Aiezuddin; Mohd Zahir, Zaznuriah; Zaharifudin, Sara Zuriati (2007)
This paper attempts to inform the public on the knowledge and scope of IHL. A general overview of IHL is highlighted in this paper. Readers will obtain a general idea of what IHL is from discussions made based on selected treaties and conventions, specifically under the four Geneva Conventions of 1949. Moreover, this paper seeks to analyze to what extent Malaysia has fulfilled its obligations as a State to ensure respect of the law in times of peace or when necessary, during armed conflict. Furthermore, this paper includes relevant provisions concerning the obligations which Malaysia acceded under the Geneva Conventions. Having being a signatory to the GC, Malaysia has a duty to comply with the Articles that it has acceded. Therefore, it is the objective of this paper to analyze the existing laws and efforts that has been made by the government and any other relevant bodies, in ensuring compliance to the law. In completion of this paper, among others the writers found that there have been attempts to disseminate IHL by the government and other relevant bodies. However, the idea of dissemination was not conducted extensively throughout the entire nation as it was only actively carried out in certain states. Additionally, since Malaysia is not a party to the ICC, it does not have jurisdiction to prosecute war criminals. As such, this will be a detriment to Malaysia where future circumstances call for such jurisdiction.